A Primer to Clinical Genome Sequencing - Priest, James R (Curr Opin Pediatr, 2017)
PURPOSE OF REVIEW: Genome sequencing is now available as a clinical diagnostic test. There is a significant knowledge and translation gap for non-genetic specialists of the processes necessary to generate and interpret clinical genome sequencing. The purpose of this review is to provide a primer on contemporary clinical genome sequencing for non-genetic specialists describing the human genome project, current techniques and applications in genome sequencing, limitations of current technology, and techniques on the horizon. RECENT FINDINGS: As currently implemented, genome sequencing compares short pieces of an individual’s genome to a reference sequence developed by the human genome project. Genome sequencing may be used for obtaining timely diagnostic information, cancer pharmacogenomics, or in clinical cases when previous genetic testing has not revealed a clear diagnosis. At present, the implementation of clinical genome sequencing is limited by the availability of clinicians qualified for interpretation, and current techniques in used clinical testing do not detect all types of genetic variation present in a single genome. SUMMARY: Clinicians considering a genetic diagnosis have wide array of testing choices which now includes genome sequencing. Though not a comprehensive test in its current form, genome sequencing offers more information than gene-panel or exome sequencing and has the potential to replace targeted single-gene or gene-panel testing in many clinical scenarios.